Identification of an Interaction between the TPα and TPβ Isoforms of the Human Thromboxane A(2) Receptor with Protein Kinase C-related Kinase (PRK) 1: IMPLICATIONS FOR PROSTATE CANCER - Turner, Elizebeth C. (American Society for Biochemistry and Molecular Biology, 2011)
In humans, thromboxane (TX) A(2) signals through the TPα and TPβ isoforms of the TXA(2) receptor or TP. Here, the RhoA effector protein kinase C-related kinase (PRK) 1 was identified as an interactant of both TPα and ΤPβ involving common and unique sequences within their respective C-terminal (C)-tail domains and the kinase domain of PRK1 (PRK1(640–942)). Although the interaction with PRK1 is constitutive, agonist activation of TPα/TPβ did not regulate the complex per se but enhanced PRK1 activation leading to phosphorylation of its general substrate histone H1 in vitro. Altered PRK1 and TP expression and signaling are increasingly implicated in certain neoplasms, particularly in androgen-associated prostate carcinomas. Agonist activation of TPα/TPβ led to phosphorylation of histone H3 at Thr(11) (H3 Thr(11)), a previously recognized specific marker of androgen-induced chromatin remodeling, in the prostate LNCaP and PC-3 cell lines but not in primary vascular smooth muscle or endothelial cells. Moreover, this effect was augmented by dihydrotestosterone in androgen-responsive LNCaP but not in nonresponsive PC-3 cells. Furthermore, PRK1 was confirmed to constitutively interact with TPα/TPβ in both LNCaP and PC-3 cells, and targeted disruption of PRK1 impaired TPα/TPβ-mediated H3 Thr(11) phosphorylation in, and cell migration of, both prostate cell types. Collectively, considering the role of TXA(2) as a potent mediator of RhoA signaling, the identification of PRK1 as a bona fide interactant of TPα/TPβ, and leading to H3 Thr(11) phosphorylation to regulate cell migration, has broad functional significance such as within the vasculature and in neoplasms in which both PRK1 and the TPs are increasingly implicated.